Analysis of Factors Affecting the Poverty Rate in Nusa Tenggara Barat Province for the Period 2018-2022 - Ni Nengah Yuni Widya Pratiwi; Sahri , Sahri; Tuti Handayani (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to analyse the factors that influence the poverty rate in Nusa Tenggara Barat Province in 2018-2022. This research uses a quantitative method with an associative approach. The type of data used is secondary data. Data sources were obtained from the Central Bureau of Statistics of Nusa Tenggara Barat Province. The research location is in Nusa Tenggara Barat Province with 10 districts / cities. The data analysis used is panel data regression analysis.  The results showed that (1), partially population has a negative and significant effect on the poverty rate in Nusa Tenggara Barat Province. (2), partially education has a negative and insignificant effect on the poverty rate in Nusa Tenggara Barat Province. (3) Partially, minimum wage has a negative and insignificant effect on the poverty rate in Nusa Tenggara Barat Province. (4) Partially, unemployment has a negative and insignificant effect on the poverty rate in Nusa Tenggara Barat Province. (5) Simultaneously, the variables of population, education, minimum wage, and unemployment together have a significant effect on the poverty rate in Nusa Tenggara Barat Province.